636.IMPLEMENTATION OF ADVANCED CONTROL METHODS FOR IMPROVED VEHICLE DYNAMICS AND SAFETY USING CO-SIMULATION APPROACH - Vasko, Cangoski; Igor, Djurkov; Vase, Jordanoska (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2021)
The increasing application of mechatronic devices in everyday life increases the demands for higher reliability and safety in order to achieve more sustainable systems. Inspired by the enormous efforts put in decreasing the number of accidents on the roads which is attributed to implementation of improved mechatronic systems, a controller for improved vehicle dynamics was created and comparison between two advanced control methods was made. Improved vehicle dynamics and stability control system is mandatory for most vehicles, and in order to make contribution in this field, a cascade controller for selective wheel braking control is implemented in a virtual 3D vehicle model. By using sliding mode control (SMC) and Linear Quadratic Regulator (LQR) as adopted control methods, an improved vehicles dynamics is achieved and also a more reliable system is created due to the adaptiveness of the control strategies. Using co-simulation approach involving ADAMS/Car and Matlab/Simulink, results for standardized vehicle maneuvers are obtained and the benefits of the proposed controllers are analyzed.